Deterministic six states protocol for quantum communication - Shamsul Shaari, Jesni; Lucamarini, Marco; Wahiddin, Mohamed Ridza (Elsevier, 2006)
We consider a two-way deterministic protocol for quantum communication using six mutually unbiased states in the Poincaré sphere. The logical information is encoded by flip or not-flip operations on the states. Despite the nonexistence of a universal flip gate the protocol saturates the bound of a unitary efficiency. Three eavesdropping strategies are analyzed suggesting better probabilities of detecting an unauthorized adversary.